A comprehensive method of diagnosing turboprop engines - Єнчев, С.В.; Гуз, С.Ю.; Олалі, Майкл; Вознюк, А.П. (Proceedings of National Aviation University (archive), 2007)
The possibility of using minimum criteria-parametric characteristics of complex method to diagnose turboprop engines will be considered.